Introduction to feedback control. - Qiu, Li, ....-; Zhou, Kemin, ....- (Upper Saddle River : Pearson, 2010)
For undergraduate courses in control theory at the junior or senior level. Introduction to Feedback Control, First Editionupdates classical control theory by integrating modern optimal and robust control theory using both classical and modern computational tools. This text is ideal for anyone looking for an up-to-date book on Feedback Control. Although there are many textbooks on this subject, authors Li Qiu and Kemin Zhou provide a contemporary view of control theory that includes the development of modern optimal and robust control theory over the past 30 years. A significant portion of well-known classical control theory is maintained, but with consideration of recent developments and available modern computational tools.